Investigation of VRB-ESS integrated with renewable hybrid power system for building - Chen, Wenguang. (2014)
Beneficial in items of improved reliability, energy services, operational life and energy efficiency, VRB-ESS and its integrated hybrid power system has brought forth the better form of perfection in generation and distribution.